2011
DOI: 10.1116/1.3532826
|View full text |Cite
|
Sign up to set email alerts
|

Electrical analysis of three-stage passivated In0.53Ga0.47As capacitors with varying HfO2 thicknesses and incorporating an Al2O3 interface control layer

Abstract: The atomic layer deposition of high dielectric constant oxides like HfO2 on III-V substrates such as In0.53Ga0.47As leads to a poor interface, with the growth of In0.53Ga0.47As native oxides regardless of the surface pretreatment and passivation method. The presence of the native oxides leads to poor gate leakage current characteristics due to the low band gap of the native oxides and the presence of potential wells at the interface. In addition, the poor quality of this interface leads to very large interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Obviously, post remote-plasma treatments employed in this work have also assisted to inhibit the formation of the native defect states that correlated to the interface trap density [14]. Utilizing the AlN-IPL pre-treatment and the remote-plasma post-treatment in an in situ PEALD process, the strong inversion behaviors can be achieved for HfO 2 /InGaAs devices with relative low EOT and D it values as compared to other literature reports [4], [11], [15][16][17].…”
Section: Resultsmentioning
confidence: 79%
“…Obviously, post remote-plasma treatments employed in this work have also assisted to inhibit the formation of the native defect states that correlated to the interface trap density [14]. Utilizing the AlN-IPL pre-treatment and the remote-plasma post-treatment in an in situ PEALD process, the strong inversion behaviors can be achieved for HfO 2 /InGaAs devices with relative low EOT and D it values as compared to other literature reports [4], [11], [15][16][17].…”
Section: Resultsmentioning
confidence: 79%
“…Suzuki et al, 104 O'Mahony et al, 105,106 and Kim et al 107 recently found a decrease in D it for depositing monolayers of Al2O3 before HfO2 in a GaAs:oxide gate stack. This carries over from other viewpoints.…”
Section: E Makes Complex Reconstructions Involving Numerous Layersmentioning
confidence: 99%
“…Following the etching of the InAs/GaAs to form the active area of the device, and 10% (NH 4 ) 2 S surface passivation, the Al 2 O 3 (15 nm) top-gate oxide was formed by ALD. The ALD process is also reported to be effective in reducing or removing native oxides present on the III-V surface [21].…”
Section: Transistor Test Structuresmentioning
confidence: 99%